Use of a stent to treat colonic stenosis secondary to acute pancreatitis: A case report. (2019) - Kimura, Jiro; Lefor, Alan Kawarai; Fukai, Shota; Kubota, Tadao
Highlights: A colonic stent was used to treat colonic stenosis secondary to acute pancreatitis. Surgery should be postponed until the inflammation and obstruction improve. Use of enteric stents could be used as a temporizing measure before surgery. Abstract: Introduction: We report a patient for whom a colonic stent was successfully used to treat colonic stenosis secondary to acute pancreatitis. Presentation of case: A 70-year-old male presented with epigastric pain. A choledocholith and bile duct dilatation were found on abdominal computed tomography scan. Endoscopic retrograde cholangiopancreatography was performed and a common bile duct stent was placed. Ten hours after stent placement, severe epigastric pain developed. Contrast enhanced abdominal computed tomography scan revealed increased density of fat tissue around the pancreas. He was diagnosed with severe acute pancreatitis and treated in the intensive care unit. On the twenty-eighth hospital day, he vomited. His abdomen was distended and tender to palpation. Contrast enhanced abdominal computed tomography scan revealed stenosis of the descending colon and proximally dilated colon and small bowel. He was diagnosed with colonic stenosis secondary to acute pancreatitis. A colonic stent was placed in the descending colon. Eight months after this episode, elective subtotal colectomy was performed. The postoperative course was unremarkable. Discussion: The overall documented leak rate for segmental colectomy with or without on-table lavage following large bowel obstruction is about 4%. In addition, in the acute phase of severe acute pancreatitis, inflammation makes surgery difficult. Use of enteric stents in patients with pancreatitis could be used as a temporizing measure until the inflammation and obstruction improve. Conclusion: Colonic stenting is useful as a bridge to surgery in the management of large bowel obstruction.